Analysis of Indonesian Economic Growth using System Generalized Method of Moment - Ramadhan, Gilang; Yunitasari, Duwi; Priyono, Teguh Hadi (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
This study aims to examine the short-term and long-term impacts of household consumption, domestic investment, foreign investment, and government expenditure on regional economic growth across 34 provinces in Indonesia from 2013 to 2022. The method employed is dynamic panel regression using the System Generalized Method of Moments (SYS-GMM). Our result shows that household consumption significantly and positively affects regional economic growth in both the short and long-term. Domestic investment shows a positive impact but is not statistically significant in either the short or long-term. Conversely, foreign investment exhibits a negative impact that is also not statistically significant over both time horizons. Government expenditure demonstrates a positive and significant impact on regional economic growth in both the short and long-term. Effective government policies are therefore necessary across the 34 provinces to foster both domestic and foreign investment.